2018
DOI: 10.5935/0103-507x.20180035
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal sympathetic hyperactivity syndrome caused by fat embolism syndrome

Abstract: Paroxysmal sympathetic hyperactivity represents an uncommon and potentially life-threatening complication of severe brain injuries, which are most commonly traumatic. This syndrome is a clinical diagnosis based on the recurrent occurrence of tachycardia, hypertension, diaphoresis, tachypnea, and occasionally high fever and dystonic postures. The episodes may be induced by stimulation or may occur spontaneously. Underdiagnosis is common, and delayed recognition may increase morbidity and long-term disability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The theorized biologic mechanism is that corticosteroids stabilize the phospholipid bilayer comprising cell members, thereby limiting free fatty acid levels and inhibiting complement-mediated leukocyte aggregation [ 1 ]. Despite this, the use of steroids is controversial, and further examination of the same trial showed no difference in mortality compared to control patients receiving standard prevention and supportive treatment [ 1 , 3 , 6 , 11 ]. Still, based on this study, some clinicians utilize methylprednisolone 6-90 mg/kg as FES prophylaxis in patients with long bone fractures [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The theorized biologic mechanism is that corticosteroids stabilize the phospholipid bilayer comprising cell members, thereby limiting free fatty acid levels and inhibiting complement-mediated leukocyte aggregation [ 1 ]. Despite this, the use of steroids is controversial, and further examination of the same trial showed no difference in mortality compared to control patients receiving standard prevention and supportive treatment [ 1 , 3 , 6 , 11 ]. Still, based on this study, some clinicians utilize methylprednisolone 6-90 mg/kg as FES prophylaxis in patients with long bone fractures [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic symptoms are the most common and occur in 85% of cases [ 1 , 7 ]. CFE is a sequela of FES and is diagnosed when neurological involvement is either seen on imaging or is the main symptomatic manifestation of the disease [ 3 , 6 ]. The condition occurs when fat emboli are scattered into the cerebral microvasculature with disruption of the blood-brain barrier and subsequent cerebral ischemia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These symptoms are consistent with certain autopsy results that show hemorrhaging and inflammation near petechiae sites dispersed through white matter tracts, likely caused by fat globules obstructing brain microvasculature [ 12 - 14 ]. Furthermore, fat emboli may localize to central areas that control catecholamine release, thereby explaining the specific association between CFE, increased catecholamine blood levels, and paroxysmal sympathetic hyperactivity (PSH) [ 12 , 15 ]. PSH can be clinically observed and include features such as tachycardia, hypertension, tachypnea, irregular motor tone, and hyperthermia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%